Impacts of increased bioenergy demand on global food markets: an AgMIP economic model intercomparison. (10th December 2013) - Lotze‐Campen, Hermann; von, Martin; Kyle, Page; Fujimori, Shinichiro; Havlik, Petr; van, Hans; Hasegawa, Tomoko; Popp, Alexander; Schmitz, Christoph; Tabeau, Andrzej; Valin, Hugo; Willenbockel, Dirk; et al.
Abstract Integrated Assessment studies have shown that meeting ambitious greenhouse gas mitigation targets will require substantial amounts of bioenergy as part of the future energy mix. In the course of the Agricultural Model Intercomparison and Improvement Project (AgMIP), five global agro‐economic models were used to analyze a future scenario with global demand for ligno‐cellulosic bioenergy rising to about 100 ExaJoule in 2050. From this exercise a tentative conclusion can be drawn that ambitious climate change mitigation need not drive up global food prices much, if the extra land required for bioenergy production is accessible or if the feedstock, for example, from forests, does not directly compete for agricultural land. Agricultural price effects across models by the year 2050 from high bioenergy demand in an ambitious mitigation scenario appear to be much smaller (+5% average across models) than from direct climate impacts on crop yields in a high‐emission scenario (+25% average across models). However, potential future scarcities of water and nutrients, policy‐induced restrictions on agricultural land expansion, as well as potential welfare losses have not been specifically looked at in this exercise.